Analisis Internal Perencanaan Strategis Di SMPN 2 Ngawi dalam Mewujudkan Sekolah Adiwiyata (Perspektif SWOT) - Kalimah, Siti; Abdullah, Mudhofir; Makruf, Imam; Purnomo, Siddiq (Universitas Muhammadiyah Ponorogo, 2022)
This field research is descriptive qualitative. examines the problem of Internal Analysis of Strategic Planning at SMPN 2 Ngawi with a SWOT perspective. The purpose of this research is to see the internal strengths and weaknesses at SMPN 2 Ngawi and to see the results of internal and external analysis using SWOT analysis in an effort to formulate a strategic plan design (renstra). Research data obtained using the method of observation, interviews. and archiving (documentation studies). Findings from this study: based on the final IFAS score: 1.80 and the final EFAS score: 0.80. Using the SWOT diagram analysis, the calculation results on the strength opportunity (SO) position support the aggressive strategy (SO) in strategic planning development. Strategic plans that need to be developed in an effort to realize the Adiwiyata school at SMPN 2 Ngawi: 1) Implementation of reliable PLH program management; 2) Integration of PLH insights on all subjects; 3) Establish partnerships with BPOM and related departments in the management of food safety programs; 4) Establish partnerships with the education office and the community in implementing PLH, 5) Capacity building of human resources in relation to PLH insights.